Stakeholders’ Participation in the Constituency Development Catalyst Fund Projects in Tanzania - Mwigune, Dinno; Kamugisha, Dennis; Ringo, Cliford (Journal of Policy and Leadership, 2025)
With a focus on Tanzania's Dodoma Urban and Itilima constituencies, this study investigates the involvement of stakeholders in projects funded by the Constituency Development Catalyst Fund (CDCF). The study used a qualitative case study design, guided by stakeholders' theory. Interviews, focus groups, document reviews, and observation were used to gather data, which was then subjected to content analysis. The results demonstrate that while both constituencies had comparable patterns of participation during preliminary planning, they diverged during execution. In contrast to the instrumental perspective of stakeholders' theory, citizens' participation in the planning phase was restricted to voting for proposed projects rather than determining project needs. Participation took the form of contributions and involvement in CDCF committees during implementation. Participation levels varied: in Dodoma Urban, contributions from urban wards were lower than those from peri-urban wards and Itilima; similarly, CDCF committee participation was higher in Itilima and Dodoma Urban's peripheral wards than in its urban wards. According to the study's findings, CDCF participation is still low, which is in line with Arnstein's ladder's lower levels. Instead of just supporting proposals from street and village councils, it suggests reviewing policies and guidelines to allow stakeholders to actively participate in project identification.